2006
DOI: 10.1051/forest:2006017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing streamwater composition on sandstone (Vosges Mountains)

Abstract: -The influence of sandstone composition, precipitation, vegetation and relief on streamwater composition at base flow was studied in 95 forested catchments located in the sandstone part of the Vosges Mountains (N.E. France). Catchments lie on four main types of sandstone. Information was acquired for each catchment using a geographic information system (GIS) and spatially distributed databases. Sulphate concentration is mainly negatively correlated to the annual rainfall and positively to the relative area cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, predictive ability of these models can vary widely when applied to different portions of the landscape. Models predicting ANC by Berg et al [2005] and models predicting ANC, Ca, and Mg by Nedeltcheva et al [2006a, 2006b] showed wide variation in their R 2 values when applied to areas differing in size or geology, respectively. In both cases, models for some portions of the landscape had performance similar to ours, but models of other areas were much weaker.…”
Section: Discussionmentioning
confidence: 99%
“…However, predictive ability of these models can vary widely when applied to different portions of the landscape. Models predicting ANC by Berg et al [2005] and models predicting ANC, Ca, and Mg by Nedeltcheva et al [2006a, 2006b] showed wide variation in their R 2 values when applied to areas differing in size or geology, respectively. In both cases, models for some portions of the landscape had performance similar to ours, but models of other areas were much weaker.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have suggested explanations for the temporal and spatial variability of stream CQ relationships. Such relationships may be controlled by organic matter and solute source mass distribution [Hood et al, 2006;Herndon et al, 2015], geomorphic regime [Kasahara and Wondzell, 2003;Torres et al, 2015;Ward et al, 2016], anthropogenic contributions [Basu et al, 2010;Thompson et al, 2011;Musolff et al, 2015], water residence time [Tetzlaff et al, 2009;Maher, 2011], subsurface flow paths [Anderson et al, 1997;Mulholland and Hill, 1997], seasonality [Butturini and Sabater, 2000], storm events [Hill, 1993;Kirchner, 2003;Zimmer and Lautz, 2014], bedrock lithology [Bluth and Kump, 1994;Hattanji and Onda, 2004;Nedeltcheva et al, 2006;Ibarra et al, 2016], and cation exchange [Clow and Mast, 2010]. Depending on catchment characteristics, stream solute concentrations can remain constant (''chemostatic'') or can change (''chemodynamic'') in response to changes in stream discharge [McDonnell, 2003;Andrea et al, 2006;Godsey et al, 2009;Thompson et al, 2011;Kirchner and Neal, 2013;Musolff et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Soil mineral weathering: Soil mineralogy was computed from total soil analysis and general information on soil minerals on sandstone (Nedeltcheva et al, 2006). We used the thoroughly tested and validated geochemical model PROFILE (Sverdrup and Warfvinge, 1988) calibrated with the SP57 soil solution concentrations to calculate this annual input.…”
Section: Site Presentationmentioning
confidence: 99%